Pius VI, Pont.Max. engraving BNF Gallica - Unknown Unknown.... (Wikimedia Commons, 2013)
Notice iconographique issue de Wikimedia Commons. Titre: Pius VI, Pont.Max. engraving BNF Gallica. Pius VI (1717 - 1799), 250th pope of the Roman Catholic Church.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie